Educational program of organ donation and transplantation at medical school - Garcia, Clotilde Druck; Goldani, João Carlos; Brandão, Ajácio; Haussen, Sérgio Roberto; Neumann, Jorge; Chem, Eduardo; Lucchese, Fernando; Frota Filho, José Dario; Marcon, Alexandre; Vitola, Santo Pascoal; et al. (Brazilian Journal of Transplantation, 2009)
Purpose: The purpose of our program is to supply basic knowledge on organ donation and transplantation to students of Medicine, Nutrition and Biomedicine, aiming to increase their knowledge on donation and transplantation and to qualify them to spread information, and enhance their commitment to this process to produce a positive response to increase the insufficient amount of donors. Methods: The premature education of students in their careers. In order to supply the necessary information on the donation–transplantation process, a Medical School associated to the Hospital Transplant Coordination Department has created an educational program of Organ Donation and Transplantation. This course aims medical, biomedical and nutrition students. Each semester 50 to 90 students are enrolled in the course, involving a total of 25 hours. Various aspects are discussed, such as brain death, donor management, political and legal aspects of the donation, skin, lung, bone marrow, heart, pancreas, liver and kidney transplantation. Results: Students rated the course as excellent, concluding that it contributed to their education. Their attitude towards organ donation and transplantation was strongly positive at the end of the course. Conclusion: A favorable attitude of the health professionals to organ donation can positively influence the decision of families of potential donors. This project aims to educate and stimulate students in the organ donation-transplantation process and it should be implemented in other Medical Schools.